Interpeler l’absent. - Marie-Laure Florea (Corela)
This article deals with the discursive and pragmatic functioning of the direct address to the deceased in the obituaries appearing in French press. This process may seem surprising in this genre of discourse, insofar as the person who is being addressed is inevitably excluded of the communicative situation, due to the context. This article has a dual purpose: first, it identifies the part played by direct address to the deceased in the obituary, proving that it aims at reembodying the dead person, in order to bind the community, at the very moment it is threatened by silence. Furthermore, this article intends to redefine the contours of the notion of direct address, in particular within the frame of enunciation theory: direct address has most of the time two recipients, the addressee, which is namely mentioned in the term of address, and the audience, whom the discourse is not addressed, but which is, by means of a communicative trope, the real intended recipient.